A high strength 6082 aluminum alloy

By preparing carbon fiber-doped reinforced phase A and reinforced phase B of high-entropy alloy, combined with heat treatment and ball milling technology, the problem of insufficient strength of traditional 6082 aluminum alloy is solved, and the mechanical properties and stability of the aluminum alloy are significantly improved.

CN119464974BActive Publication Date: 2025-04-01GUANGZHOU GOLDEN ALUMINUM ALUMINUM
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510065355.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-01
Estimated Expiration
2045-01-16

AI Technical Summary

Technical Problem

Traditional 6082 aluminum alloy has insufficient strength in actual applications, which is difficult to meet the requirements of automotive load strength design, and has low hardness during the extrusion process and unstable mechanical properties.

Method used

By preparing two reinforced phases A and reinforced phase B, carbon fiber doping and high-entropy alloys were used respectively, and combined with heat treatment and ball milling processes, a high-strength 6082 aluminum alloy was formed.

Benefits of technology

It significantly improves the tensile strength and elongation of aluminum alloy, enhances mechanical properties and stability, and meets the design requirements of automobile load strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a high-strength 6082 aluminum alloy, and relates to the technical field of alloys. When preparing the high-strength 6082 aluminum alloy, the invention first uses aluminum chloride, titanium tetrachloride, chromium chloride, cerium nitrate, and lanthanum nitrate as precursors, and carbon fiber is doped, and a reinforcement phase A is prepared after heat treatment. Secondly, aluminum powder, titanium powder, copper powder, chromium powder, and manganese powder are used to prepare a high entropy alloy as a reinforcement phase B. Finally, the reinforcement phase A, the reinforcement phase B, and aluminum alloy powder are mixed to prepare an aluminum alloy. The high-strength 6082 aluminum alloy prepared by the invention has good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of alloys, in particular to a high-strength 6082 aluminum alloy. Background Art

[0002] Aluminum alloy has become an important lightweight material in the automotive industry due to its low density, good plasticity, and good specific strength. It is widely used in the manufacture of automotive frame structural parts, suspension systems, etc. However, with the development of society, users have higher and higher requirements for lightweight aluminum materials for automobiles, requiring aluminum materials to have certain strength and good plasticity. However, in the actual extrusion process, aluminum alloys often have low hardness, and their mechanical properties cannot meet the standards after natural or artificial aging. When used for load-bearing structures, their strength sometimes cannot meet the design requirements of automotive load strength, which may cause structural deformation; the strength performance of traditional 6082 aluminum alloy needs to be improved, which limits its wider application. Summary of the invention

[0003] The purpose of the present invention is to provide a high-strength 6082 aluminum alloy and a preparation method and application thereof, so as to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] A high-strength 6082 aluminum alloy, wherein the preparation method of the aluminum alloy comprises the following preparation steps:

[0006] (1) Preparation of reinforcing phase A: Aluminum chloride, titanium tetrachloride, chromium chloride, cerium nitrate, and lanthanum nitrate in a molar ratio of 1:(0.7-0.8):(1.1-1.2):(0.5-0.7):(0.5-0.7) were dissolved in anhydrous ethanol 10-12 times the mass of aluminum chloride, and carbon fiber 2-3 times the mass of aluminum chloride was added and ultrasonically treated for 15 min to obtain solution A. Under argon protection, 5 mol / L sodium hydroxide solution with a volume of 0.75 times the volume of anhydrous ethanol and 50 wt% ammonia water with a volume of 0.75 times the mass of anhydrous ethanol were mixed and heated to 160°C to obtain solution B. Solution A was added dropwise to solution B at 160°C and stirred for 60 min. After stirring, the mixture was filtered and washed with anhydrous ethanol 3 times, heat treated in a tube furnace, cooled, and ball milled to obtain reinforcing phase A.

[0007] (2) Preparation of reinforcing phase B: Weigh the alloy powder, place it in a sealed container, and place it on a V-type powder mixer for 10-12 hours. Pour the mixed powder into a ball mill with a ball-to-material ratio of 8:1. After evacuating and introducing nitrogen, start ball milling. After ball milling for 60 hours, dry it in a drying oven to obtain reinforcing phase B.

[0008] (3) Cold pressing: Reinforcement phase A, reinforcement phase B, and 6082 aluminum alloy powder are mixed, and the ball mill is filled with argon gas for protection; finally, the mixed powder is ball milled at a speed of 160 r / min for 90 min, and then placed in a mold and cold pressed on a hydraulic press at a pressure of 60 MPa to obtain a block material;

[0009] (4) Sintering: Place the bulk material in a high-temperature resistance furnace, heat it to 100°C at a heating rate of 5°C / min, and keep it at that temperature for 30 minutes; then, heat it to 250°C at a heating rate of 5°C / min, keep it at that temperature for 30 minutes, and then heat it to 450°C at a heating rate of 5°C / min, and then heat it again at 3°C / min, and keep it at that temperature for 35 minutes; finally, cool it to 450°C at a rate of 3°C / min and cool it in the furnace to obtain an alloy precursor;

[0010] (5) Hot pressing: The alloy precursor is hot pressed to obtain high-strength 6082 aluminum alloy.

[0011] Preferably, the heat treatment process in step (1) is: in an atmosphere of 10% hydrogen and 90% argon, heating from 30°C to 250°C at a heating rate of 10°C / min, and keeping at 250°C for 30 minutes.

[0012] Preferably, the mesh size of the reinforcing phase A in step (1) is 300 meshes.

[0013] Preferably, the alloy powder in step (2) is composed of the following raw materials: 3% aluminum powder, 21% titanium powder, 24% copper powder, 36% chromium powder, and 16% manganese powder; the mesh size of the alloy powder is 300 mesh.

[0014] Preferably, the ball mill in step (2) is a planetary ball mill with a rotation speed of 200 r / min.

[0015] Preferably, in step (3), the mass ratio of the reinforcement phase A, the reinforcement phase B, and the 6082 aluminum alloy powder is 5:10:85.

[0016] Preferably, the hot pressing process in step (5) is set as follows: hot pressing temperature is 600° C., pressure is 30 MPa, loading speed is 10 mm / s, and holding time is 5 s.

[0017] Preferably, the carbon fiber in step (1) is 3 mm chopped carbon fiber with a diameter of 7 μm.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] When preparing high-strength 6082 aluminum alloy, the present invention prepares two reinforcing phases for reinforcing the aluminum alloy; firstly, aluminum chloride, titanium tetrachloride, chromium chloride, cerium nitrate, and lanthanum nitrate are used as precursors, carbon fibers are doped, and an alloy carbon-based reinforcing phase is prepared after heat treatment, the carbon fibers are uniformly distributed in the precursor solution, and a multi-element alloy is generated in situ on the fiber surface after heat treatment, and the alloy generated in situ on the fiber surface is more densely combined with the fiber interface; at the same time, the composite material composed of the fiber and the alloy is better than the single alloy in terms of mechanical properties and stability, and secondly, aluminum powder, titanium powder, copper powder, chromium powder, and manganese powder are prepared into a high-entropy alloy as a reinforcing phase B, titanium powder and chromium powder are refractory elements and are often used to prepare lightweight high-entropy alloys, and can be used together with manganese and copper to simultaneously form The hard solid solution and the soft solid solution are formed, and the high strength of the refractory high entropy alloy is maintained while the plastic toughness is improved; finally, the reinforcing phase A, the reinforcing phase B, and the aluminum alloy powder are mixed to prepare the aluminum alloy. The reinforcing phase A and the reinforcing phase B have the same aluminum, titanium, and chromium elements, and the interface bonding between the two is good. The rare earth elements cerium and lanthanum in the reinforcing phase A can refine the grains in the alloy and enhance the mechanical properties of the aluminum alloy. The elastic fibers in the reinforcing phase A can not only play a role in load transfer, but also improve the strength of the alloy and play a role in crack connection and crack deflection. Since the surface of the carbon fiber is an alloying element, in the process of preparing the aluminum alloy with the aluminum alloy powder, the problem of poor wettability of the interface between the traditional carbon fiber and the aluminum alloy can be well solved, thereby forming a clean and well-bonded interface. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] The carbon fibers described in the following examples and comparative examples are 3 mm chopped carbon fibers with a diameter of 7 μm. Example 1

[0022] A high-strength 6082 aluminum alloy, wherein the preparation method of the high-strength 6082 aluminum alloy comprises the following preparation steps:

[0023] (1) Preparation of reinforcing phase A: Aluminum chloride, titanium tetrachloride, chromium chloride, cerium nitrate, and lanthanum nitrate in a molar ratio of 1:0.7:1.1:0.5:0.5 were dissolved in anhydrous ethanol twice the mass of aluminum chloride, and carbon fiber twice the mass of aluminum chloride was added and ultrasonically treated for 15 min to obtain solution A. Under argon protection, 5 mol / L sodium hydroxide solution with a volume of 0.75 times that of anhydrous ethanol and 50 wt% ammonia water with a volume of 0.75 times that of anhydrous ethanol were mixed and heated to 40 ℃. The mixture was heated to 160°C to obtain a solution B. Solution A was added dropwise to solution B at 160°C and stirred for 60 min. After stirring, the mixture was filtered and washed with anhydrous ethanol for 3 times. The mixture was heat treated in a tube furnace. The heat treatment process parameters were as follows: in an atmosphere of 10% hydrogen and 90% argon, the temperature was increased from 30°C to 250°C at a rate of 10°C / min. The mixture was kept at 250°C for 30 min. After cooling, the reinforcement phase A was obtained by ball milling. The mesh number of the reinforcement phase A was 300 meshes.

[0024] (2) Preparation of reinforcing phase B: Weigh alloy powder, which is composed of the following raw materials: 3% aluminum powder, 21% titanium powder, 24% copper powder, 36% chromium powder, and 16% manganese powder. The alloy powder has a mesh size of 300 mesh. Place it in a sealed container and place it on a V-type powder mixer for 12 hours. Pour the mixed powder into a ball mill with a ball-to-material ratio of 8:1. After evacuating and introducing nitrogen, start ball milling. The ball mill is a planetary ball mill with a rotation speed of 200 r / min. After ball milling for 60 hours, dry it in a drying oven to obtain reinforcing phase B.

[0025] (3) Cold pressing: Reinforcement phase A, reinforcement phase B, and 6082 aluminum alloy powder are mixed, and the mass ratio of reinforcement phase A, reinforcement phase B, and 6082 aluminum alloy powder is 5:10:85; the ball mill is filled with argon gas for protection; finally, the mixed powder is ball milled at a speed of 160r / min for 90min, and then placed in a mold and cold pressed on a hydraulic press at a pressure of 60MPa to obtain a block material;

[0026] (4) Sintering: Place the bulk material in a high-temperature resistance furnace, heat it to 100°C at a heating rate of 5°C / min, and keep it at that temperature for 30 minutes; then, heat it to 250°C at a heating rate of 5°C / min, keep it at that temperature for 30 minutes, and then heat it to 450°C at a heating rate of 5°C / min, and then heat it again at 3°C / min, and keep it at that temperature for 35 minutes; finally, cool it to 450°C at a rate of 3°C / min and cool it in the furnace to obtain an alloy precursor;

[0027] (5) Hot pressing: The alloy precursor is hot pressed to obtain high-strength 6082 aluminum alloy; the hot pressing process parameters are: hot pressing temperature 600°C, pressure 30 MPa, loading speed 10 mm / s, and holding time 5 s. Example 2

[0028] A high-strength 6082 aluminum alloy, wherein the preparation method of the high-strength 6082 aluminum alloy comprises the following preparation steps:

[0029] (1) Preparation of reinforcing phase A: Aluminum chloride, titanium tetrachloride, chromium chloride, cerium nitrate, and lanthanum nitrate in a molar ratio of 1:0.75:1.15:0.6:0.6 were dissolved in anhydrous ethanol with a mass of 11 times that of aluminum chloride, and carbon fiber with a mass of 2.5 times that of aluminum chloride was added and ultrasonically treated for 15 min to obtain solution A. Under argon protection, 5 mol / L sodium hydroxide solution with a volume of 0.75 times that of anhydrous ethanol and 50 wt% ammonia water with a volume of 0.75 times that of anhydrous ethanol were mixed. The temperature was raised to 160°C to obtain solution B. Solution A was added dropwise to solution B at 160°C and stirred for 60 minutes. After stirring, the mixture was filtered and washed with anhydrous ethanol for 3 times. The mixture was heat treated in a tube furnace. The heat treatment process parameters were as follows: in an atmosphere of 10% hydrogen and 90% argon, the temperature was raised from 30°C to 250°C at a rate of 10°C / min. The mixture was kept at 250°C for 30 minutes. After cooling, the mixture was ball milled to obtain a reinforcement phase A. The mesh number of the reinforcement phase A was 300 meshes.

[0030] (2) Preparation of reinforcing phase B: Weigh alloy powder, which is composed of the following raw materials: 3% aluminum powder, 21% titanium powder, 24% copper powder, 36% chromium powder, and 16% manganese powder. The alloy powder has a mesh size of 300 mesh. Place it in a sealed container and place it on a V-type powder mixer for 11 hours. Pour the mixed powder into a ball mill with a ball-to-material ratio of 8:1. After evacuating and introducing nitrogen, start ball milling. The ball mill is a planetary ball mill with a rotation speed of 200 r / min. After ball milling for 60 hours, dry it in a drying oven to obtain reinforcing phase B.

[0031] (3) Cold pressing: Reinforcement phase A, reinforcement phase B, and 6082 aluminum alloy powder are mixed, and the mass ratio of reinforcement phase A, reinforcement phase B, and 6082 aluminum alloy powder is 5:10:85; the ball mill is filled with argon gas for protection; finally, the mixed powder is ball milled at a speed of 160r / min for 90min, and then placed in a mold and cold pressed on a hydraulic press at a pressure of 60MPa to obtain a block material;

[0032] (4) Sintering: Place the bulk material in a high-temperature resistance furnace, heat it to 100°C at a heating rate of 5°C / min, and keep it at that temperature for 30 minutes; then, heat it to 250°C at a heating rate of 5°C / min, keep it at that temperature for 30 minutes, and then heat it to 450°C at a heating rate of 5°C / min, and then heat it again at 3°C / min, and keep it at that temperature for 35 minutes; finally, cool it to 450°C at a rate of 3°C / min and cool it in the furnace to obtain an alloy precursor;

[0033] (5) Hot pressing: The alloy precursor is hot pressed to obtain high-strength 6082 aluminum alloy; the hot pressing process parameters are: hot pressing temperature 600°C, pressure 30 MPa, loading speed 10 mm / s, and holding time 5 s. Example 3

[0034] A high-strength 6082 aluminum alloy, wherein the preparation method of the high-strength 6082 aluminum alloy comprises the following preparation steps:

[0035] (1) Preparation of reinforcing phase A: Aluminum chloride, titanium tetrachloride, chromium chloride, cerium nitrate, and lanthanum nitrate in a molar ratio of 1:0.8:1.2:0.7:0.7 were dissolved in anhydrous ethanol 12 times the mass of aluminum chloride, and carbon fiber 3 times the mass of aluminum chloride was added and ultrasonically treated for 15 min to obtain solution A. Under argon protection, 5 mol / L sodium hydroxide solution with a volume of 0.75 times the volume of anhydrous ethanol and 50 wt% ammonia water with a volume of 0.75 times the mass of anhydrous ethanol were mixed and heated to 40 ℃. The mixture was heated to 160°C to obtain a solution B. Solution A was added dropwise to solution B at 160°C and stirred for 60 min. After stirring, the mixture was filtered and washed with anhydrous ethanol for 3 times. The mixture was heat treated in a tube furnace. The heat treatment process parameters were as follows: in an atmosphere of 10% hydrogen and 90% argon, the temperature was increased from 30°C to 250°C at a rate of 10°C / min. The mixture was kept at 250°C for 30 min. After cooling, the reinforcement phase A was obtained by ball milling. The mesh number of the reinforcement phase A was 300 meshes.

[0036] (2) Preparation of reinforcing phase B: Weigh alloy powder, which is composed of the following raw materials: 3% aluminum powder, 21% titanium powder, 24% copper powder, 36% chromium powder, and 16% manganese powder. The alloy powder has a mesh size of 300 mesh. Place it in a sealed container and place it on a V-type powder mixer for 10 hours. Pour the mixed powder into a ball mill with a ball-to-material ratio of 8:1. After evacuating and introducing nitrogen, start ball milling. The ball mill is a planetary ball mill with a rotation speed of 200 r / min. After ball milling for 60 hours, dry it in a drying oven to obtain reinforcing phase B.

[0037] (3) Cold pressing: Reinforcement phase A, reinforcement phase B, and 6082 aluminum alloy powder are mixed, and the mass ratio of reinforcement phase A, reinforcement phase B, and 6082 aluminum alloy powder is 5:10:85; the ball mill is filled with argon gas for protection; finally, the mixed powder is ball milled at a speed of 160r / min for 90min, and then placed in a mold and cold pressed on a hydraulic press at a pressure of 60MPa to obtain a block material;

[0038] (4) Sintering: Place the bulk material in a high-temperature resistance furnace, heat it to 100°C at a heating rate of 5°C / min, and keep it at that temperature for 30 minutes; then, heat it to 250°C at a heating rate of 5°C / min, keep it at that temperature for 30 minutes, and then heat it to 450°C at a heating rate of 5°C / min, and then heat it again at 3°C / min, and keep it at that temperature for 35 minutes; finally, cool it to 450°C at a rate of 3°C / min and cool it in the furnace to obtain an alloy precursor;

[0039] (5) Hot pressing: The alloy precursor is hot pressed to obtain high-strength 6082 aluminum alloy; the hot pressing process parameters are: hot pressing temperature 600°C, pressure 30 MPa, loading speed 10 mm / s, and holding time 5 s.

[0040] Comparative Example 1:

[0041] The preparation method of the high-strength 6082 aluminum alloy of Comparative Example 1 differs from that of Example 2 in that step (1) is not included, and step (3) is modified as follows: cold pressing: reinforcing phase B and 6082 aluminum alloy powder are mixed, and the mass ratio of reinforcing phase B and 6082 aluminum alloy powder is 10:90; the ball mill is filled with argon gas for protection; finally, the mixed powder is ball milled at a speed of 160 r / min for 90 minutes on the ball mill, and then placed in a mold, and cold pressed on a hydraulic press at a pressure of 60 MPa to obtain a block material.

[0042] Comparative Example 2:

[0043] The preparation method of the high-strength 6082 aluminum alloy of Comparative Example 2 differs from that of Example 2 in that step (2) is not included, and step (3) is modified as follows: cold pressing: reinforcing phase A and 6082 aluminum alloy powder are mixed, with the mass ratio of reinforcing phase A to 6082 aluminum alloy powder being 5:95; the ball mill is filled with argon gas for protection; finally, the mixed powder is ball milled at a speed of 160 r / min for 90 min on the ball mill, and then placed in a mold, and cold pressed on a hydraulic press at a pressure of 60 MPa to obtain a block material.

[0044] Test example:

[0045] Mechanical properties test method: The tensile strength and elongation are tested to evaluate the mechanical properties of the prepared ultra-high strength 6082 aluminum alloy. The specific test method is as follows: Refer to GB / T 228.1-2021 for mechanical properties test. The sample length is 140mm, the width is 18mm, the gauge length is 40mm, the thickness is 3mm, and the tensile speed is 3mm / min. The tensile strength and elongation are tested. Each group of 5 samples is tested and the average value is recorded. The results are shown in Table 1.

[0046] Table 1 Statistics of mechanical properties test results

[0047]

[0048] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-2 in Table 1, it can be found that the ultra-high strength 6082 aluminum alloy prepared by the present invention has good tensile strength and elongation. By comparison, the addition of reinforcement phase A and reinforcement phase B improves the mechanical properties of the aluminum alloy.

[0049] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A high-strength 6082 aluminum alloy, characterized in that: The preparation method of the aluminum alloy comprises the following preparation steps: (1) Preparation of reinforcing phase A: Aluminum chloride, titanium tetrachloride, chromium chloride, cerium nitrate, and lanthanum nitrate in a molar ratio of 1:(0.7-0.8):(1.1-1.2):(0.5-0.7):(0.5-0.7) were dissolved in anhydrous ethanol 10-12 times the mass of aluminum chloride, and carbon fiber 2-3 times the mass of aluminum chloride was added and ultrasonically treated for 15 min to obtain solution A. Under argon protection, 5 mol / L sodium hydroxide solution with a volume of 0.75 times the volume of anhydrous ethanol and 50 wt% ammonia water with a volume of 0.75 times the mass of anhydrous ethanol were mixed and heated to 160°C to obtain solution B. Solution A was added dropwise to solution B at 160°C and stirred for 60 min. After stirring, the mixture was filtered and washed with anhydrous ethanol 3 times, heat treated in a tube furnace, cooled, and ball milled to obtain reinforcing phase A. (2) Preparation of reinforcing phase B: Weigh alloy powder, which is composed of the following raw materials: 3% aluminum powder, 21% titanium powder, 24% copper powder, 36% chromium powder, and 16% manganese powder; the alloy powder has a mesh size of 300 mesh; place it in a sealed container and place it on a V-type powder mixer for 10-12 hours. Pour the mixed powder into a ball mill with a ball-to-material ratio of 8:

1. After evacuating and introducing nitrogen, start ball milling. After ball milling for 60 hours, dry it in a drying oven to obtain reinforcing phase B. (3) Cold pressing: Reinforcement phase A, reinforcement phase B, and 6082 aluminum alloy powder are mixed, and the mass ratio of reinforcement phase A, reinforcement phase B, and 6082 aluminum alloy powder is 5:10:85; the ball mill is filled with argon gas for protection; finally, the mixed powder is ball milled at a speed of 160r / min for 90min, and then placed in a mold and cold pressed on a hydraulic press at a pressure of 60MPa to obtain a block material; (4) Sintering: Place the bulk material in a high-temperature resistance furnace, heat it to 100°C at a heating rate of 5°C / min, and keep it at that temperature for 30 minutes; then, heat it to 250°C at a heating rate of 5°C / min, keep it at that temperature for 30 minutes, and then heat it to 450°C at a heating rate of 5°C / min, and then heat it again at 3°C / min, and keep it at that temperature for 35 minutes; finally, cool it to 450°C at a rate of 3°C / min and cool it in the furnace to obtain an alloy precursor; (5) Hot pressing: The alloy precursor is hot pressed to obtain high-strength 6082 aluminum alloy.

2. A high-strength 6082 aluminum alloy according to claim 1, characterized in that: The heat treatment process in step (1) is: in an atmosphere of 10% hydrogen and 90% argon, heating from 30°C to 250°C at a heating rate of 10°C / min, and keeping at 250°C for 30 minutes.

3. The high-strength 6082 aluminum alloy according to claim 1, characterized in that: The mesh size of the reinforcing phase A in the step (1) is 300 meshes.

4. The high-strength 6082 aluminum alloy according to claim 1, characterized in that: The ball mill in step (2) is a planetary ball mill with a rotation speed of 200 r / min.

5. The high-strength 6082 aluminum alloy according to claim 1, characterized in that: The hot pressing process in step (5) is set as follows: hot pressing temperature is 600° C., pressure is 30 MPa, loading speed is 10 mm / s, and holding time is 5 s.

6. The high-strength 6082 aluminum alloy according to claim 1, characterized in that: The carbon fiber in step (1) is 3 mm chopped carbon fiber with a diameter of 7 μm.

Citation Information

Patent Citations

  • Silicon carbide reinforced aluminum-based composite material and preparation method thereof

    CN109576522A

  • High-strength light aluminum-based composite material and preparation method thereof

    CN112391560A